2007
DOI: 10.1007/s10552-007-9003-y
|View full text |Cite
|
Sign up to set email alerts
|

NSAIDs and breast cancer recurrence in a prospective cohort study

Abstract: Our findings provide support for an inverse association between current, regular ibuprofen use and breast cancer recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(106 citation statements)
references
References 20 publications
3
100
3
Order By: Relevance
“…32 Our results are consistent with two other studies reported in 2007. Kwan et al 33 reported on NSAID use and recurrence among 2,292 women with early-stage breast cancer. They found a reduced risk of recurrence for current regular (Ն 3 days per week) use of ibuprofen (RR ϭ 0.56; 95% CI, 0.32 to 0.98) but not aspirin (RR ϭ 1.09; 95% CI, 0.74 to 1.61); short follow-up (5 years) may have precluded detecting an association.…”
Section: Discussionmentioning
confidence: 99%
“…32 Our results are consistent with two other studies reported in 2007. Kwan et al 33 reported on NSAID use and recurrence among 2,292 women with early-stage breast cancer. They found a reduced risk of recurrence for current regular (Ն 3 days per week) use of ibuprofen (RR ϭ 0.56; 95% CI, 0.32 to 0.98) but not aspirin (RR ϭ 1.09; 95% CI, 0.74 to 1.61); short follow-up (5 years) may have precluded detecting an association.…”
Section: Discussionmentioning
confidence: 99%
“…Ibuprofen and aspirin are attractive intervention agents as both are affordable non-specific COX-2 inhibitors that can be used for decades with minimal side effects. In fact, COX-2 is considered a viable target for prevention and treatment in a variety of cancers (Thun et al, 1991;Elder & Paraskeva, 1998;Kwan et al, 2007;Holmes et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Kwan et al [102] examined the association between NSAID use and breast cancer recurrence among 2292 women diagnosed with breast cancer in the Life After Cancer Epidemiology Study. They observed that regular ibuprofen users experienced 44% less recurrence than non-users after five years of follow-up.…”
Section: Therapeutic Studies Of Nsaids In Human Breast Cancermentioning
confidence: 99%